Comparative Analysis of the Developmental Toxicity in Xenopus laevis and Danio rerio Induced by Al2O3 Nanoparticle Exposure. (16th October 2019) - Ismail, Tayaba; Lee, Hyun‐Kyung; Kim, Chowon; Kim, Youni; Lee, Hongchan; Kim, Jun‐Hyeong; Kwon, Song; Huh, Tae‐Lin; Khang, Dongwoo; Kim, Sang‐Hyun; Choi, Sun‐Cheol; Lee, Hyun‐Shik
Abstract: Engineered aluminum oxide nanoparticles (Al2 O3 NPs) having high‐grade thermal stability and water‐dispersion properties are extensively used in different industries and personal care products. Toxicological response evaluation of these NPs is indispensable in assessing the health risks and exposure limits because of their industrial disposal into the aquatic environment. We assessed and compared the developmental toxicity of Al2 O3 NPs in Xenopus laevis and Danio rerio over a period of 96 h using the frog embryo teratogenic assay Xenopus and a fish embryo toxicity assay. Engineered Al2 O3 NP exposure produced dose‐dependent embryonic mortality and decreased the embryo length, indicating a negative effect on growth. Moreover, Al2 O3 NPs induced various malformations, such as small head size, a bent/deformed axis, edema, and gut malformation, dose‐dependently and altered the expression of heart‐ and liver‐specific genes in both X. laevis and D. rerio, as revealed by whole‐mount in‐situ hybridization and reverse transcriptase polymerase chain reaction. In conclusion, the toxicological data suggest that Al2 O3 NPs are developmentally toxic and teratogenic and negatively affect the embryonic development of X. laevis and D. rerio . Our study can serve as a model for the toxicological evaluation of nanomaterial exposure on vertebrate development that is critical to ensure human and environmental safety. Environ Toxicol Chem 2019;38:2672–2681. © 2019 SETAC